Use of Different Dosages of Gonadotrophine Hormones For Java Combtail (Belontia hasselti) Spawning Semi Naturally - Danang Yonarta; Ingka Selviana; Tanbiyaskur Tanbiyaskur; Dwi Inda Sari (Universitas Batangahari Jambi, 2023)
Java combtail (Belontia hasselti) is a fish originating from swamps that is widely used by the community and needs to be developed through hatchery cultivation. The Kelekar II Farmer Group in Burai Village, Tanjung Batu District, Ogan Ilir Regency is one of the farmer groups that still relies on seasonal harvests from nature. Excessive agility fishing activities can threaten the extinction of the java combtail population. Research purpose to determine the effect of giving different gonadotrophine hormone on the semi-natural spawning of java combtail (Belontia hasselti) in Burai village, Tanjung Batu District. This research was carried out in Burai Village, North Indralaya, Ogan Ilir Regency, South Sumatra, in September-November 2022. The spawning of the java combtail used a different dose in treatment 1 (P1) by injecting the gonadotropin hormone at a dose of 0.3 ml kg-1 fish weight and treatment 2 (P2) by injecting gonadotropin hormone dose of 0.5 ml kg-1 fish weight. The research results obtained the best dose of 0.5 ml kg-1 resulting produced a fecundity at 2.677 eggs, hatching time at 24 hours, fertilization rate at 75%, hatching rate at 93% and Survival Rate (SR) at 80.8%. Water quality obtained in this research activity is a temperature ranged from 25.9-32.0 oC, pH 5.1-6.65, DO 3.1-6.65 mg L-1 and ammonia 0.051-0.121 mg L-1.